Tanggung Gugat atas Tindakan Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) yang Melakukan Pemblokiran Rekening Dormant Nasabah Perbankan - Sandy Resa Ramadhan; Tahegga Primananda Alfath (Jurnal Ilmu Sosial dan Humaniora, 2026)
Financial Transaction Reports and Analysis Center (PPATK), as an independent institution authorized to prevent and eradicate money laundering (TPPU) when blocking dormant accounts (passive accounts) belonging to banking customers. This blocking is often carried out without any strong initial indication of TPPU, based solely on passive criteria that are feared to become a means of concealing illegal funds. Although PPATK's actions have a legal basis in Law No. 8 of 2010, its implementation causes material and non-material losses for customers whose accounts are blocked, especially for customers who are compliant and not involved in criminal activities. The normative-empirical research method is used to examine related laws and regulations, field practices, and court decisions. The research results indicate that, theoretically, the PPATK's liability can be enforced through an unlawful act lawsuit (PMH) under Article 1365 of the Civil Code, considering that disproportionate and unreasonable blocking can be categorized as an arbitrary act (detournement de pouvoir) that violates the customer's fundamental rights. Furthermore, administrative and criminal liability can also potentially be applied if there is negligence or abuse of authority in the blocking process. These findings emphasize the importance of establishing more specific dormant criteria and establishing clear and expeditious objection and recovery procedures for aggrieved customers, in order to maintain a balance between efforts to eradicate financial crime and protect customers' civil rights.